Juan Mayorga : six plays - Mayorga, Juan; Johnson, Jerelyn; Johnston, David (Professor) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Juan Mayorga: Six Plays is the first collection of Spanish dramatist Juan Mayorga's plays in English, offering a compelling insight into the extraordinary range and quality of one of the Spanish-speaking world's most distinctive voices. The six plays are presented in translations that are both readable and eminently performable. Each is accompanied by a translator's note that discusses the strategies and decisions used in making the play performable in English as well as the play's key themes. The book also features an introduction to Mayorga's life and work, emphasising his commitment to plays whose range of forms and innovative theatre-making practice re-imagines the nature of theatre and performance each time anew. The plays themselves are brilliant treatises on our times, inspiring conversation about and critical examination of our troubled world. These scripts will be of interest to professional practitioners but are no less suited to both university and amateur settings, making this the definitive collection of Mayorga's work in English for theatremakers, students, and scholars"--
Action, emotion, poetry, and thought : introduction to Juan Mayorga and his work / Jerelyn Johnson -- Theater, translation, and philosophy / David Johnston -- Way to heaven (Himmelweg) -- The boy at the back -- Perpetual peace -- The mapmaker -- Reykjavik -- The collection.
Keywords: Mayorga, Juan -- Translations into English; Spanish drama -- Translations into English; Spanish drama -- 21st century; PERFORMING ARTS / Theater / General; PERFORMING ARTS / Theater / Playwriting